Association of CDKN2A/CDKN2B with inflammatory bowel disease in Koreans. Issue 4 (5th February 2018) - Lee, Ho‐Su; Lee, Soo Bin; Kim, Byoung Mok; Hong, Myunghee; Jung, Seulgi; Hong, Jeonghoon; Baek, Jiwon; Han, Buhm; Oh, Seak Hee; Kim, Kyung Mo; Park, Sang Hyoung; Yang, Suk‐Kyun; et al.
Abstract: Background and Aim: CDKN2A/CDKN2B locus on 9p21 is reported to be associated with various diseases, including cancer and cardiovascular and inflammatory diseases. Significant downregulation of CDKN2B‐AS1 in inflamed colon tissue of inflammatory bowel disease (IBD) cases was reported in Europeans. This study aimed to confirm the suggestive association of CDKN2A/CDKN2B with IBD identified in our recent genome‐wide association study (GWAS). Methods: We examined the association of CDKN2A/CDKN2B locus with IBD in an additional sample of 574 IBD cases and 542 controls, totaling 4068 cases and 8074 controls. In silico study was performed at various levels for functional annotation of the causal variant. Co‐localization of the GWAS association signals and the corresponding expression quantitative trait loci in IBD‐related tissues was evaluated using eCAVIAR. Results: An expanded GWAS showed genome‐wide significant association of rs3731257 at 9p21 with IBD (odds ratio = 1.17, 95% confidence interval = 1.12–1.22, P combined  = 5.68 × 10 −9 ) and Crohn's disease (odds ratio = 1.22, 95% confidence interval = 1.15–1.28, P combined  = 8.85 × 10 −9 ) in the Korean population. Co‐localization study suggested that both CDKN2B‐AS1 and CDKN2A might be functionally associated with the locus in the small intestine. Conclusions: rs3731257 in CDKN2A/CDKN2B is an IBD‐susceptible locus in Koreans, with a suggestive role for small intestine‐specific gene regulation. Our findings suggested that alterations of the CDKN2A/CDKN2B locus could affect the pathophysiology of IBD.